The correlation between T helper type 17 cells and clinical characters in Chinese paediatric patients with chronic hepatitis B - Zhu, S.; Zhang, H.; Dong, Y.; Xu, Z.; Chen, D.; Wang, L.; Gan, Y.; Wang, F.; Wang, Y.; Xing, X.; Hu, S.; Li, Z.; et al. (Clinical and experimental immunology, 2013)
Summary Interleukin (IL)‐17‐mediated immune response has been shown to play a critical role in inflammation‐associated disease. However, its role in the pathogenesis of chronic hepatitis B virus (HBV) in paediatric patients remains unknown. We investigated the frequency of T helper type 17 (Th17) cells and evaluated the association between the Th17 and clinical characters in paediatric patients with chronic hepatitis B (CHB). The frequency of Th17 cells was detected by flow cytometry analyses from 65 paediatric patients with CHB and nine healthy controls. The degree of hepatic inflammation was graded using the histological activity index (HAI). Compared with healthy controls, the frequency of Th17 cells in peripheral blood was significantly higher in paediatric patients with CHB. The proportion of Th17 cells was higher in the patients with higher HAI score (G2–G3) compared to those subjects with lower HAI score (G0–G1), but the frequency of Th17 cells had no correlation with serum HBV DNA loads or alanine aminotransferase levels. Compared with the younger age group (age 1–6 years), Th17 cell frequency was higher in the older age group (age 7–18 years). Peripheral Th17 cell frequency is associated closely with inflammation activity of liver tissues in paediatric patients with CHB.